Partial credit guarantee and financial additionality for smallholders coffee cooperatives: experience from Ethiopia. Issue 8 (17th November 2022) - Gurmessa, Negussie Efa; Ndinda, Catherine; Agwanda, Charles; Akiri, Morris
ABSTRACT: This study examined the effects of a partial credit guarantee in increasing lending to credit constrained farmer cooperatives under the Ethiopian context. The data were generated through questionnaire survey, key informant interviews, focus group discussions, and from banks' and cooperatives' records. The scheme improved financial additionality among the targeted cooperatives, but it had limited reach and impacts on terms and conditions of loans. Factors related to borrower cooperatives, lending banks, scheme design and operation, regulatory and business environments affect its effectiveness. This calls for broader interventions that enable loan guarantees to be effectively utilised and generate the desired outcomes.